Microwaves in dispersive magnetic composite media (Review Article): Оптика и магнитооптика - Tarapov, S.I.; Belozorov, D.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Review discusses some special questions of physics of composite media (metamaterials), which are formed by elements made from natural materials of two kinds. The first ones are “carriers of permittivity” and are presented by plasma-like media and semiconductors. The second ones are “carriers of permeability” — they are presented by ferromagnets. Among such ferromagnets are ferrodielectrics (ferrites) and manganite-perovskite compounds. In the first chapter of the review some principal aspects of the electrodynamics of periodical structures — magnetophotonic crystals are considered. The questions of zone structure and possible violations of periodicity (Tamm states, defect mode) as well as the influence of external magnetic field on the spectral characteristics of magnetophotonic crystals are considered. The second chapter of the review is devoted to the electrodynamics of left-handed media (left-handed metamaterials). Different versions of composite left-handed media are considered. Particular attention is paid to features of electrodynamics of artificially synthesized lefthanded media, the doped lanthanum manganites-perovskites, which in a certain concentrations of doping element and temperature range can serve as an example of natural left-handed media. The Appendix describes the details of experimental techniques radiophysical research. Note that the research and design of the metamaterials listed above in a range of low temperatures are particularly important. This is due to the fact that at low temperatures a main disadvantage of artificial materials mentioned above (quite large losses) becomes less noticeable. At the same time the main their advantage (namely the possibility to control their frequency dispersion) remains. Thus it seems that the most prospective areas of application and further study of the magnetic metamaterials lie at low temperatures.